2004
DOI: 10.4049/jimmunol.172.1.464
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivation of STAT3 Is Involved in Abnormal Differentiation of Dendritic Cells in Cancer

Abstract: Abnormal differentiation of myeloid cells is one of the hallmarks of cancer. However, the molecular mechanisms of this process remain elusive. In this study, we investigated the effect of tumor-derived factors on Janus kinase (Jak)/STAT signaling in myeloid cells during their differentiation into dendritic cells. Tumor cell conditioned medium induced activation of Jak2 and STAT3, which was associated with an accumulation of immature myeloid cells. Jak2/STAT3 activity was localized primarily in these myeloid ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
307
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 406 publications
(323 citation statements)
references
References 30 publications
11
307
1
4
Order By: Relevance
“…Previous studies implicated STAT6 as possible factor involved in immune suppression associated with myeloid cells (14,41,42). We have demonstrated important role of STAT3 in accumulation of Gr-1 ϩ IMC in cancer (13), and a number of groups demonstrated important role of STAT1 in regulation of iNOS activity (43,44). Present study demonstrated that increased STAT6 activity in TAM was not responsible for their immunosuppressive activity.…”
Section: Figurementioning
confidence: 55%
See 3 more Smart Citations
“…Previous studies implicated STAT6 as possible factor involved in immune suppression associated with myeloid cells (14,41,42). We have demonstrated important role of STAT3 in accumulation of Gr-1 ϩ IMC in cancer (13), and a number of groups demonstrated important role of STAT1 in regulation of iNOS activity (43,44). Present study demonstrated that increased STAT6 activity in TAM was not responsible for their immunosuppressive activity.…”
Section: Figurementioning
confidence: 55%
“…Hyperactivation of Jak2-STAT3 pathway was recently implicated in abnormal myeloid cell differentiation and function in cancer (13,32). Elevated level of STAT3 activity was observed in different myeloid cells isolated from tumor-bearing mice (13).…”
Section: Role Of Stat Transcription Factors In Tam-mediated T Cell Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Leptin activates the JAK-STAT signaling pathway, and an optimal level of STAT3 activation is critically important for normal DC differentiation [19]. With Western blot analysis of sorting-purified viable splenic CD11c + MHC-II + immature DC and LPS-matured DC, phosphorylated STAT3 was shown to be markedly reduced in immature db/db DC, whereas a moderate reduction was observed in mature db/db DC (Fig.…”
Section: Impaired Signaling Pathways In Db/db DCmentioning
confidence: 95%